(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2010)
Formation of high-temperature superconducting ceramics of composition of Bi2-xLnxSr2CaCu2Oy, was investigated. Effect of Ві replacement for La, Nd, Eu, Ho, Er, Lu on the crystalline structure and critical temperature was shown.Our XRD studies of the Bi2-хLnxSr2CaCu2Oу (Ln- La, Nd, Eu, Ho, Er, Lu) system showed that in case of Ln-La with the increase of degree of substituting for x there is an increase of parameters a and c. For Ln- Nd, Eu, Ho, Er, Lu with the increase of degree of substituting x parameters a and c decrease.Temperature of passing into the superconducting state for samples with replacement of Bi3+/ln3+ decrease, in comparison to the clean Bi2212 phase.